2016
DOI: 10.1128/mcb.00833-15
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation Regulates the Endocytic Function of the Yeast Dynamin-Related Protein Vps1

Abstract: The family of dynamin proteins is known to function in many eukaryotic membrane fusion and fission events. The yeast dynamin-related protein Vps1 functions at several stages of membrane trafficking, including Golgi apparatus to endosome and vacuole, peroxisomal fission, and endocytic scission. We have previously shown that in its endocytic role, Vps1 functions with the amphiphysin heterodimer Rvs161/Rvs167 to facilitate scission and release of vesicles. Phosphoproteome studies of Saccharomyces cerevisiae have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 65 publications
0
9
0
Order By: Relevance
“…In alpha facor arrested cells, Vps1 interacts with the septins (Renz et al, 2016). Vps1 is a dynamin related protein that functions at several stages of membrane trafficking including endocytic scission (Smaczynska-de Rooij et al, 2010, 2015). …”
mentioning
confidence: 99%
“…In alpha facor arrested cells, Vps1 interacts with the septins (Renz et al, 2016). Vps1 is a dynamin related protein that functions at several stages of membrane trafficking including endocytic scission (Smaczynska-de Rooij et al, 2010, 2015). …”
mentioning
confidence: 99%
“…The yeast BAR domain amphiphysin protein Rvs167, interacts with Vps1 and both proteins contribute to scission of endocytic vesicles 34 . In a previous study we also demonstrated interactions between Rvs167 and Vps1 that are affected by phosphorylation of Vps1 within the Insert B region, at serine 599 close to the lysine stretch [35]. Mutation of the Vps1-Rvs167 interaction site correlated with a shorter lifetime of Rvs167 association at endocytic sites.…”
Section: Resultsmentioning
confidence: 72%
“…Another rationale behind the inclusion of Vps1 at the "hot spot" is that Vps1 localizes to the late endosome and interacts with PI3P in vitro (Hayden et al, 2013;Smaczynska-de et al, 2015). ESCRT-II localization to the endosome is mediated by the N-terminal region of its Vps22/Vps36 lobe.…”
Section: Discussionmentioning
confidence: 99%
“…with the membrane-remodeling protein (Figure 2), Vps1, at the endosome (Figure 3), and that Vps1 shares a redundant role with these complexes (Figure 4), namely efficient sorting of the cargo Cps1 into ILVs. At present, the biochemical targeting mechanism of Vps1 to the endosome has not been revealed, but a recent lipid binding preference test exhibited that Vps1 strongly interacts with PI3P, which is highly enriched in the endosome (Smaczynska-de et al, 2015), pointing to a lipid-binding ability of Vps1 that may facilitate its recruitment to the endosome. In light of the finding that multiple components of the ESCRT system, including Vps22, Vps36, and Vps24, bind to Vps1, we investigated the significance of these protein factors for the recruitment of Vps1 onto the endosomal membrane.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation